Effects of Neutrophil Extracellular Traps on Bovine Mammary Epithelial Cells in vitro - Wei, Zhengkai; Wang, Jingjing; Wang, Yanan; Wang, Chaoqun; Liu, Xiao; Han, Zhen; Fu, Yunhe; Yang, Zhengtao (Frontiers in Immunology, 2019)
Bovine mastitis is a common infectious disease in dairy cattle, and bovine mammary epithelial cells damage usually directly causes economic losses related to milk production. NETs, and their novel effector mechanism, have been observed in the milk and mammary glands of sheep, but NET formation is also reported to exacerbate the pathogenesis of several inflammatory diseases. The detailed mechanism by which NETs regulate bovine mastitis remains unelaborated. Thus, we aim to examine the effects of NETs on bovine mammary epithelial cells in vitro, and further to clary the detail mechanism. In this study, the cytotoxicity of NETs on BMEC was determined using LDH Cytotoxicity Assay Kit, and the viability of cells was examined by Cell Counting Kit-8. Histone-induced bovine mammary epithelial cells damage was examined by flow cytometry and immunofluorescence analysis. The activities of caspase 1, caspase 3, caspase 11 and NLRP3 was detected using Western blot and immunohistochemical analysis. The results showed that NETs and their component histones significantly increased cytotoxicity to bovine mammary epithelial cells, which suggests the critical role of NETs and their component histones in BMEC damage. In addition, the mechanism by which NETs induce bovine mammary epithelial cells damage is apoptosis, necrosis and pyroptosis, with histone-induced bovine mammary epithelial cells pyroptosis being a caspase-1-dependent process. Taken together, NET formation regulates inflammation and bovine mammary epithelial cells damage in mastitis. Inhibiting excess NET formation may be useful to ameliorate mammary gland damage associated with mastitis.